Tulevikuresidentuur - Lumpre, Joel; Reim, Helen; Arulaane, Saara; Velgan, Marta; Antsov, Eva; Kasterpalu, Kristjan-Martin; Õunap, Elinor; Randaru, Mann; Järviste, Jaarika; Pihlak, Rille (Eesti Arst, 2019)
Eesti Arst 2019; 98(5):255–260